Disfunción de la articulación temporomandibular y su relación con maloclusiones dentarias de los y las estudiantes de 18 a 30 años de edad de la Universidad Nacional de Loja, de la modalidad de estudios presencial, en el periodo mayo-julio de 2014 - Íñiguez Fernández, Ligia Eugenia (2014)
The etiology of temporomandibular dysfunction is multifactorial nature and the presence of dental malocclusion has been widely implicated as factors for onset and perpetuation. Given this descriptive study, cross-sectional, which aimed to determine the relationship between Temporomandibular Joint Dysfunction and dental malocclusions and the students of 18-30 years of age from the National University of Loja was performed, the mode of classroom studies in the period May-July 2014 ". The results were that the Temporomandibular dysfunction was presented at a 41.49% being more frequent in females with 48.01%, the most common sign and symptom was the noise with a 21.33% frequency dental malocclusion was Class I malocclusion with 12.26% Class II malocclusions with 18.40% and Class III malocclusions with 21.06%. Finally the correlation between dysfunction of the temporomandibular joint and the presence of malocclusions Class I, II and III malocclusions, the most obvious sign of this noise articulate this relationship. Keywords: Temporomandibular Joint Dysfunction, dental malocclusion